ANALISIS YURIDIS TERHADAP PUTUSAN PERKARA NOMOR 47/PID.B/2018/PN MANDAILING NATAL PADA KORBAN SALAH TANGKAP BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1981 TENTANG KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Rangkuti, Nurul Ibda Aprilia; Indra, Mexsasai; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
One of the problems that occur in the Criminal Justice System is the violation of rights at one or all levels of examination. These violations can be in the form of procedural violations, administrative violations, personal violations of the suspect to serious violations such as the fabrication of witnesses and the fabrication of evidence of a case. If a suspect's information which is allegedly committed a criminal act is used as evidence for the investigator, it turns out that the acquisition is based on pressure or coercion that results in psychological and physical suffering and creates fear. Acquisition of information as evidence must be declared invalid because it may contain an engineered confession. Violations of procedures and misidentification of victims of criminal acts that still occur today are seen as a result of the weak professionalism of law enforcement officers. Cases of wrong procedures and wrong investigations can lead to errors in determining the culprit or what is often called a wrong arrest. This happened in Case Number 47 / Pid.B / 2018 / PN Mandailing Natal. The purpose of writing this thesis, namely: first, knowing juridical analysis of Decision Number 47 / Pid.B / 2018 / PN Mandailing Natal on victims of wrongful arrest based on Law Number 8 of 1981 concerning KUHAP. Second, knowing the basic analysis of judges' consideration of Case Decision Number 47 / Pid.B / 2018 / PN Mandailing Natal for victims of wrongful arrests under Law No. 8 of 1981 concerning KUHAP.The type of research used in this legal research is the normative juridical method. Therefore, it is used an analysis with a qualitative measure based on the substance of the data collection in drawing conclusions. In drawing conclusions the author uses the method of deductive thinking, which is a way of thinking that draws a conclusion from things that are general to things that are specific.From the results of research and discussion it can be concluded, first, the existence of law enforcement officers who are not professional in carrying out their duties in accordance with the provisions of Law No. 8 of 1981 concerning KUHAP. Second, the judge in deciding a criminal case must consider the formal requirements of evidence and regarding the strength of evidence the judge must see firsthand whether there is correspondence between one and another evidence, the judge should look at the facts that occur in the trial.Keywords: Criminal Justice System, Wrong Arrest, Decision